Endoscopic spinal discectomy/decompression: A Case Series - Luevisadpaibul, Tanapat (Samutprakan Hospital Journal (SMPK HOS J), 2023)
Lumbar intervertebral disk herniation and lumbar spinal stenosis are common causes of radiating back pain. Surgical procedure is required in some cases, those who do not respond to conservative treatment. Standard open surgery involves causing more damage to posterior spinal structures. Endoscopic spine surgery has been introduced to minimize injuries and disabilities. This study reports case series that were treated by endoscopic surgery. The result demonstrates that patients’ disabilities were significantly reduced, proven by Thai Oswestry Disability Index (Thai ODI) reduction from 40.4 to 19.6